The Immunophenotyping Changes of Peripheral CD4+ T Lymphocytes and Inflammatory Markers of Class III Obesity Subjects After Laparoscopic Gastric Sleeve Surgery – A Follow-Up Study - Nasser M Rizk (18810328) (2021)
Purpose Obesity is a chronic disorder characterized by a low-grade inflammatory state and immune cell irregularities. The study aimed to follow up on the changes in the peripheral CD4+ T lymphocytes and the pro-inflammatory cytokines; IL-6, TNF-alpha, MCP-1, and IL-10 at baseline and 12 weeks post-surgical intervention by the laparoscopic gastric sleeve (LGS) in morbidly obese patients (class III obesity subjects). Materials and Methods A prospective longitudinal research included 24 class III obesity subjects with a BMI > 40 kg/m2. The subjects were enrolled from the Metabolic/Surgical Department at Hamad Medical Corporation (HMC)-Qatar. Fasting blood samples were collected at admission to LGS for weight loss and after 12 weeks of LGS. The immunophenotype of CD4+ T-cell populations; naïve (CD45RA+and CD27+), central memory T cells (CD45RO+ and CD27+), and effector memory (CD45RO+and CD27−) and T-regulatory cell (CD4+CD25+ FoxP3+) were identified using flow cytometry. Plasma pro-inflammatory cytokines and adipokines were evaluated. A control group of lean subjects was used to compare changes of T-regulatory and inflammatory biomarkers with postoperative changes in obese patients. Results The means (SD) of age and BMI of class III obesity subjects was 32.32 (8.36) years and 49.02 (6.28) kg/m2, respectively. LGS caused a significant reduction in BMI by 32%, p< 0.0001. LGS intervention significantly decreased CD4+ T-lymphocytes and effector memory (TEM) cells but increased T-regulatory (Treg), naïve, and central memory (TCM) cells, with all p values < 0.05. The increase of Treg cells postoperative is significantly lower compared to lean subjects, p < 0.05. A significant reduction of plasma IL-6, TNF-α, and MCP-1, but IL-10 significantly increased after LGS, with all p< 0.05. Adiponectin/leptin ratio improved after LGS by 2.9 folds, p< 0.0001. Conclusion Weight loss by LGS accomplished a substantial rise of Treg and decreased EM T-lymphocytes with a shift from pro-inflammatory to the anti-inflammatory pattern. Other Information Published in: Journal of Inflammation Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/jir.s282189